Effect of a Local Laser Heat Treatment on the Formability of Multi-layered 6000 Series Aluminum Alloys - Merklein, Marion; Herrmann, Jürgen (Physics Procedia, 2016)
The production of multi-layered aluminum alloys using the Accumulative Roll Bonding Process (ARB) is an auspicious possibility to fabricate nanostructured sheet material with enhanced mechanical properties. The increased strength qualifies these semi-finished products for lightweight applications in automotive industry. However, the ARB process also leads to a reduced ductility of the ultra-fine grained material. Furthermore, failure mechanisms like delamination can occur during forming operations. A local short term laser heat treatment according to the Tailor Heat Treated Blanks technology can be applied in order to enhance the formability and prevent failure. Multi-layered sheets of the aluminum alloy AA6014 were produced in a warm rolling process. The mechanical properties as well as the bond strength are investigated within this contribution using tensile tests and T-peel tests. The material characterization is carried out in dependency of the heat treatment temperature. Air bending tests in combination with a local laser heat treatment are used in order to investigate the formability of the multi-layered aluminum sheets.
EAM Import::2019-03-14